Early and severe onset of esophageal dysfunction after laparoscopic sleeve gastrectomy: a case report and review of literature - Benites-Goñi, Harold (2024)
After bariatric surgery one of the most common complications is dysphagia. The etiology of this disease has not been fully elucidated but it is known that it may be due to structural changes due to surgery. This case describes a 65-year-old female with early and severe onset of dysphagia following laparoscopic sleeve gastrectomy. The patient's final diagnosis was postobesity surgery esophageal dysfunction and laparoscopic proximal gastrectomy with esophagojejunal Roux-en-Y anastomosis was performed. Physicians should be aware of this condition in order to offer early diagnosis and treatment.